Adolescent’s Adjustment to Family Dynamics in Delhi: A Comparative Analysis by Gender - Rahul Singhal; Sangeeta Kakkar; Ritika Chauhan (International Journal of Children, 2025)
This study examined adolescents' adjustment to their family environments, drawing on a sample of 200 participants (100 boys and 100 girls), aged 16 to 18 years, selected through convenience sampling from the Delhi region. Data was collected using the "Family Environment Inventory" and the "Adjustment Inventory for School Students" (1993). Statistical analysis was performed using SPSS 26, applying tools such as mean, standard deviation (SD), t-tests, and Pearson’s Product Moment Correlation. The findings revealed no appreciable gender differences in home environment characteristics such cohesion, expressiveness, conflict, acceptance and caring, independence, active-recreational orientation, organization, control, and degrees of emotional, social, and educational adjustment. However, significant correlations were found between the adjustment levels of boys and girls with respect to their family environments. The study’s literature review incorporated research conducted over the last ten years in the field of adolescent adjustment and family dynamics, providing a comprehensive understanding of trends and gaps in this area. Despite its insights, the study faces certain limitations, including the use of a non-representative sample, geographical restrictions, a cross-sectional design, and a reliance on self-reported data, which may introduce biases. Although gender did not emerge as a significant factor influencing family environment and adjustment, the findings emphasize the importance of nurturing supportive family environments to promote positive developmental outcomes for adolescents. Future research should address these limitations by employing larger, more diverse samples and longitudinal designs to better capture the complexities of family dynamics in adolescent development.
Keywords: Delhi; adjustment; adolescent; family dynamics; gender differences; supportive environment